2006
DOI: 10.1207/s15327027hc2003_7
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Back from Social Norms Campaigns: Comparing Normative Influences to Other Predictors of Health Behaviors

Abstract: Recent health campaigns on college campuses have used a social norms approach, which suggests that one's perceptions of others' attitudes and behaviors are the key components in attitude and behavior change. However, the efficacy of social norms campaigns has been mixed. This study was conducted to assess the relationships among sociodemographics, normative perceptions, and individual attitudes on 3 health behaviors. Students at 2 universities (N = 393) completed questionnaires assessing how these variables re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Several important moderators or potential moderators were identified that should be taken into account when considering the influence of peer social norms on young people's food intake. This is in line with previous findings that the effects of social norm interventions on health behaviour are far from consistent (Cameron & Campo, 2006). It is likely that this seeming inconsistency across studies reflects the role of moderators of the relation between social norm messages and health behaviour that are not yet well understood.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several important moderators or potential moderators were identified that should be taken into account when considering the influence of peer social norms on young people's food intake. This is in line with previous findings that the effects of social norm interventions on health behaviour are far from consistent (Cameron & Campo, 2006). It is likely that this seeming inconsistency across studies reflects the role of moderators of the relation between social norm messages and health behaviour that are not yet well understood.…”
Section: Discussionsupporting
confidence: 90%
“…Together, these previous syntheses provide clear indications that social norms play a role in food intake (Robinson, Blisset, et al, 2013;Robinson, Thomas, et al, 2014) and provide an account of the (evolutionary) mechanisms explaining why human beings follow social norms related to eating (Higgs, 2015). However, the potential for social norms to improve health behaviour, including food intake, is by no means ubiquitous, with various studies also showing null effects or even negative results (for an overview, see Cameron & Campo, 2006). Due to potential publication bias, it is possible that additional unpublished studies exist that also showed no relation between social norms and food intake.…”
Section: Towards An Understanding Of Moderatorsmentioning
confidence: 90%
“…Other studies found that the average number of drinking days per month ranged from 4.34 to 10 [19][20][21]. These statistics compare very well with the average drinking rates from our simulations (see Figures 3-7).…”
Section: Discussionsupporting
confidence: 88%
“…Larimer and Cronce compiled data from many studies used to measure the effectiveness of prevention programs and found that many programs do not provide significant benefit [28]. Additionally, Cameron and Campo found that the like or dislike of drinking was the most influential factor in determining a person's attitude [21]. One possible extension of the program is to add variables that track weekly comparisons of abstinence rates and monitor the effects of varying the degree of attitude adjustments resulting from friends' experiences.…”
Section: Figurementioning
confidence: 99%
“…Factors other than perceived norms identified for alcohol use among higher education students include gender, alcohol expectancies and drinking motives, perceived harm, other substance use and academic discipline (Borsari et al, 2007;Cameron and Campo, 2006;Kuntsche et al, 2004;Sher and Rutledge, 2007;Webb et al, 1997).…”
mentioning
confidence: 99%